In vivo Degradation of Three-Dimensional Silk Fibroin Scaffolds - Wang, Yongzhong (2008)
Three-dimensional porous scaffolds prepared from regenerated silk fibroin using either an all aqueous process or a process involving an organic solvent, hexafluoroisopropanol (HFIP) have shown promise in cell culture and tissue engineering applications. However, their biocompatibility and in vivo degradation has not been fully established. The present study was conducted to systematically investigate how processing method (aqueous vs. organic solvent) and processing variables (silk fibroin concentration and pore size) affect the short-term (up to 2 months) and long-term (up to 1 year) in vivo behavior of the protein scaffolds in both nude and Lewis rats. The samples were analyzed by histology for scaffold morphological changes and tissue ingrowth, and by real-time RT-PCR and immunohistochemistry for immune responses. Throughout the period of implantation, all scaffolds were well-tolerated by the host animals and immune responses to the implants were mild. Most scaffolds prepared from the all aqueous process degraded to completion between two and six months, while those prepared from organic solvent (hexafluoroisopropanol (HFIP)) process persisted beyond one year. Due to widespread cellular invasion throughout the scaffold, the degradation of aqueous-derived scaffolds appears to be more homogeneous than that of HFIP-derived scaffolds. In general and especially for the HFIP-derived scaffolds, a higher original silk fibroin concentration (e.g. 17%) and smaller pore size (e.g. 100–200 µm) resulted in lower levels of tissue ingrowth and slower degradation. These results demonstrate that the in vivo behavior of the three-dimensional silk fibroin scaffolds is related to the morphological and structural features that resulted from different scaffold preparation processes. The insights gained in this study can serve as a guide for processing scenarios to match desired morphological and structural features and degradation time with tissue-specific applications.